Specific Oscillatory Power Changes and Their Efficacy for Determining Laterality in Mesial Temporal Lobe Epilepsy: A Magnetoencephalographic Study - Tanoue, Yuta; Uda, Takehiro; Hoshi, Hideyuki; Shigihara, Yoshihito; Kawashima, Toshiyuki; Nakajo, Kosuke; Tsuyuguchi, Naohiro; Goto, Takeo (Frontiers in Neurology, 2021)
Objective: Appropriate determination of the epileptic focus and its laterality is important for the diagnosis of mesial temporal lobe epilepsy (MTLE). The aims of this study were to establish a specific oscillatory distribution and laterality of the oscillatory power in unilateral MTLE with frequency analysis of magnetoencephalography (MEG). Material and Methods: Thirty-five patients with MTLE [left(LtMTLE):16, right (RtMTLE):19] and 102 healthy control volunteers (CTR) were enrolled. Oscillatory powers were compared among groups for each frequency band. Next, to compare the lateralization of oscillatory powers between LtMTLEs and RtMTLEs, the laterality index (LI) was calculated at frontal, temporal, parietal and occipital regions in each frequency band. Results: There were areas with significant oscillatory power difference between the MTLE and CTR. In most bands, there were marked increases at the parietal lobe, especially on the affected side of MTLE. Compared with CTR, LIs were significantly higher at 24/28 regions in LtMTLE, but lower at 4/28 regions and higher at 10/28 regions in RtMTLE. LI at the temporal lobe in the theta band was significantly higher in LtMTLE and significantly lower in RtMTLE. Comparing LtMTLE and RtMTLE, there were significant LI differences at most regions and frequency (21/28 regions). Significance: Using MEG frequency analysis, the characteristics of oscillatory power distribution in MTLE were demonstrated. Compared with CTR, LIs shifted to the side of the epileptic focus at the temporal lobe in the theta band. These results might provide useful additional information for determining the laterality of the focus.